Etika Profesi Hukum: Landasan Moral dalam Menegakkan Tanggung Jawab dan Keadilan di Indonesia - Dharmalinga, Inge Nur Az’zahra Maheswari; Lewoleba, Kayus Kayowuan (Media Hukum Indonesia (MHI), 2025)
Ethical values are not only owned by one or two individuals, these values come from every community group, even from the smallest group, such as family to nation, and it is expected that these groups will have a set of values to regulate their lives together. In the legal field, professional ethics are standards that regulate how a person behaves in their work. Ethics in the legal profession helps professionalism and ensures that justice can be upheld honestly and fairly. Substantial equality and orientation towards the interests and order of human life. In this case, ethics emphasizes its discussion on the constitution regarding the good and bad of human behavior. The method used in this study is Descriptive Analysis Research, which is a method used to describe or depict the subject being studied through data or events with conclusions. Ethics consist of character, nature, and morality. Advocates, individuals or groups, depending on ethics, relate to values related to how to carry out the profession of advocate for the benefit of individuals or groups. To maintain public trust in the justice system, legal professions such as advocates, judges, prosecutors, and notaries are very responsible. Indonesia, as a country of law, sets standards to maintain order